DEVELOPMENT OF MANAGEMENT IN THE HIGHER EDUCATION SYSTEM USING INNOVATIVE METHODS - Karimov, Muzaffar Abdumalikovich; Akhmadjonova, Sanobar (Educational Research in Universal Sciences, 2023)
The demand for innovation in higher education management and leadership has been increasing worldwide. This trend has been accelerated by global events such as the COVID-19 pandemic and technological advancements. The use of business models, theories, and methods like the Education Management Information System (EMIS) has improved data collection, analysis, interpretation, storage, and retrieval to make well-informed decisions. However, further research is needed to ensure that best practices, evidence, and data-driven methods are used to improve staff and student satisfaction and performance. Studies show that there is a strong positive correlation between innovation and better educational management and leadership. Leaders and educational management can be trained through conferences and benchmarking activities to increase openness to change and stakeholder happiness. By using emerging technology and promoting openness to change through education, awareness creation, and training, innovation in universities and other higher education institutions can be increased, leading to improved performance and productivity.